Factors Associated with Hispanic Adults Attending Spanish-Language Disease Self-Management Program Workshops and Workshop Completion - Smith, Matthew Lee; Ahn, SangNam; Jiang, Luohua; Kulinski, Kristie P.; Ory, Marcia G. (Frontiers in Public Health, 2015)
.